Prosthetic and surgical approach of malpositioned implants: literature review - Marroquín Soto, Consuelo (2022)
Dental implants are a rehabilitative therapeutic option in partially or totally edentulous patients. However, there are factors that must be considered as a correct diagnosis and an exhaustive planning of the case to ensure clinical success. The placement of implants in a bad position represents a challenge for the rehabilitator and predisposes to aesthetic, phonetic, biomechanical and hygienic complications; Peri-implant diseases can develop. The present work aims to carry out a review of the literature on the surgical prosthetic approach of poorly positioned implants. Therapeutic options endorsed in the literature are reviewed to learn about the different approaches to implants when they have not been ideally located.   Keywords: Osseointegration; Dental Implants; Dental Implant-Abutment Design